Comparative Study of Cerebral Perfusion in Different Types of Decompressive Surgery for Traumatic Brain Injury - Choudhary, Suresh Kumar; Sharma, Achal (Indian Journal of Neurotrauma, 2023)
Introduction Computed tomography perfusion (CTP) brain usefulness in the treatment of traumatic brain injury (TBI) is still being investigated. Comparative research of CTP in the various forms of decompressive surgery has not yet been reported to our knowledge. Patients with TBI who underwent decompressive surgery were studied using pre- and postoperative CTP. CTP findings were compared with patient's outcome.Materials and Methods This was a single-center, prospective cohort study. A prospective analysis of patients who were investigated with CTP from admission between 2019 and 2021 was undertaken. The patients in whom decompressive surgery was required for TBI, were included in our study after applying inclusion and exclusion criteria. CTP imaging was performed preoperatively and 5 days after decompressive surgery to measure cerebral perfusion. Numbers of cases included in the study were 75. Statistical analysis was done.Results In our study, cerebral perfusion were improved postoperatively in the all types of decompressive surgery (p-value < 0.05). But association between type of surgery with improvement in cerebral perfusion, Glasgow Coma Scale at discharge, and Glasgow Outcome Scale-extended at 3 months were found to be statistically insignificant (p-value > 0.05).Conclusion CTP brain may play a role as a prognostic tool in TBI patients undergoing decompressive surgery.
Keywords: traumatic brain injury); brain CT perfusion; cerebral perfusion; decompressive surgery; Glasgow Outcome Scale-extended (GOS-E)